Analisis Aspek Leksikal dalam Talk Show Sentilan-Sentilun Edisi “Perpustakaan DPR Untuk Siapa?” - Mahsusi, Juni (Universitas Muhammadiyah Surabaya, 2024)
This research aims to describe what lexical aspects are used in Sentilan Sentilun's discourse “DPR Library for whom?” and what is most dominantly used in the discourse. This research uses a descriptive qualitative method with a discourse analysis technique. The data source in this research is Sentilan Sentilun's program